Resgate histórico e paisagístico da Praça dos Expedicionários, São João Del Rei - MG - Mundim, Aline Silva (2017)
Squares built in Brazil from the eighteenth and nineteenth centuries, especially those located along the Royal Road have a structure typical of this period, with straight lines, located close to churches and with some flower beds. The city of São João Del Rei-MG emerged in this region, more specifically in the Old Path of the Royal Road, from the gold exploration in the XVIII century. Thus, this study is aimed at the historical and landscape analysis of Expedicionarios Square, one of the squares located in the historical center of São João Del Rei-MG. The methodology used consisted of an inventive analysis associated with the subjective analysis and the indications for the preservation of gardens as historical patrimony. The study of the evolution of the area was based on the analysis of morphological changes that occurred in the square and its surroundings during the development of the city. Based on the information collected, modifications were observed, both in the structure and in the toponymy of this square. The design of the square has characteristics of eclectic style, with irregular stones in its interior and beds with geometric paths, typical of the urbanization of the late nineteenth and early twentieth century. The plants used consist mainly of ornamental trees and shrubs, without any apparent logical planning. The importance of the square is connected to the population activities in this place, as well as to the building in the pavilion above it, which influenced some of its changes, besides it is also considered a noble place of the city. Indeed, because it was the place chosen to locate the Legality Fountain, landmark in the history of São João Del Rei.